2019
DOI: 10.1002/jum.15115
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics With Attribute Bagging for Breast Tumor Classification Using Multimodal Ultrasound Images

Abstract: Objectives We aimed to develop radiomics with attribute bagging, which leverages multimodal ultrasound (US) images to improve the classification accuracy of breast tumors. Methods A retrospective study was conducted. B‐mode US, shear wave elastographic, and contrast‐enhanced US images of 178 patients with 181 tumors (67 malignant and 114 benign) were included. Radiomics with attribute bagging consisted of extraction of 1226 radiomic features and analysis of them with attribute bagging. Histologic examination r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Ultrasomics extracts high-throughput information and performs quantitative analysis with a CAD, which can objectively describe and explain the features of tumors. At present, studies have combined conventional 2D ultrasound images, shear-wave elastography (SWE) images, strain elastography images, and contrastenhanced ultrasound (CEUS) images with radiomics to detect and identify breast tumors (14,(20)(21)(22). These studies extracted high-throughput features to quantify tumor shape, hardness, and hardness heterogeneity to identify breast malignancies and benign tumors.…”
Section: Screening Diagnosis Classification and Stagingmentioning
confidence: 99%
“…Ultrasomics extracts high-throughput information and performs quantitative analysis with a CAD, which can objectively describe and explain the features of tumors. At present, studies have combined conventional 2D ultrasound images, shear-wave elastography (SWE) images, strain elastography images, and contrastenhanced ultrasound (CEUS) images with radiomics to detect and identify breast tumors (14,(20)(21)(22). These studies extracted high-throughput features to quantify tumor shape, hardness, and hardness heterogeneity to identify breast malignancies and benign tumors.…”
Section: Screening Diagnosis Classification and Stagingmentioning
confidence: 99%
“…Because the contour of the lesion on SWE was indefinite, the same region on BMUS was copied and pasted to the corresponding SWE image, and was expanded to include the "stiff rim" sign if it existed. SWE is a combination of B-model image and pseudocolor elasticity layer, algorithms presented in previous studies were employed to produce clean quantitative images that mapping the tissue stiffness as grey levels [24][25][26]. The radiomic features were extracted automatically from each BMUS and SWE image by Pyradiomics (https://pyradiomics.readthedocs.io/en/latest/index.html) (Additional le 2, Supplemental Table 1…”
Section: Us Image Acquisitionmentioning
confidence: 99%
“…Five studies have reported ultrasound-based radiomics models related to breast cancer. Those studies mainly focused on the prediction of biological behavior in invasive ductal carcinoma (IDC) [29] , the differential diagnosis between triple-negative breast cancer and fibroadenoma [30], differentiation of benign and malignant breast tumors [31,32], and the diagnosis of axillary lymph node metastasis in earlystage IDC.…”
Section: Ultrasound-based Radiomics For Breast Cancermentioning
confidence: 99%
“…d e v e l o p e d a r a d i o m i c s a p p r o a c h , leveraging multimodal ultrasound images to improve the classification accuracy of breast tumors. B-mode ultrasound, SWE, and contrast-enhanced ultrasound images of 178 patients with 181 tumors (67 malignant and 114 benign) were included [32]. A total of 1,226 radiomics features were extracted and analyzed with attribute bagging.…”
Section: Ultrasound-based Radiomics For Breast Cancermentioning
confidence: 99%